Implikasi Yuridis Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja terhadap Undang-Undang Nomor 25 Tahun 2007 tentang Penanaman Modal - Chandra Darmawan, Aditya (LPPM Universitas Ekasakti Padang, 2024)
One of the primary objectives of the state is to advance the general welfare, as mandated in Article 33 of the 1945 Constitution of the Republic of Indonesia. This article emphasizes that the economy should be organized as a collective endeavor based on the principle of kinship, and vital production sectors should be controlled by the state to ensure the welfare of the people. Furthermore, the article states that the national economy should be conducted with economic democracy principles that include efficiency, fairness, sustainability, and independence while maintaining the balance of national economic progress. On the other hand, national economic development is emphasized to proceed with democracy principles to create economic sovereignty. The government's role in advancing people's economy is further strengthened by investment policies focusing on micro, small, and medium enterprises and cooperatives as a means of societal renewal and welfare improvement. Although Indonesia holds significant potential in investment as stated in the World Bank's rankings, there are still challenges in creating a conducive investment climate. Adjustments to legislation such as the Job Creation Law are made to accelerate economic and legal development, investment, and prepare the country for potential recessions. This study focuses on the regulation of investment in Indonesia and the impact of the Job Creation Law on it.